The Relationship Between Intrinsic and Extrinsic Motivation on Organizational Citizenship Behavior (OCB) Among Teachers - Sarah Mardhiah, Selamat (2010)
The purpose of this study was to examine the relationship between intrinsic and extrinsic motivation on organizational citizenship behaviour (OCB) among teachers. Data were taken from 80 teachers from Sekolah Menengah Kebangsaan Desa Petaling (SMKDP). This study used the simple random sampling technique. The questionnaire was divided into four part, namely Part A (demographic data - 8 items), Part B (OCB - 15 items), Part C (intrinsic motivation - 10 items), and Part D (extrinsic motivation - 7 items). This study looked into frequency analysis, reliability analysis, descriptive analysis, and Pearson's correlation analysis, to test the hypotheses. The results suggested that both intrinsic motivation and extrinsic motivation were significant related to OCB, respectively. However, the research shown that only intrinsic motivation was positively influenced OCB practice.